Can Malaysia feed itself? Food security issues in Malaysia - Norhisham Hassan; Kam, Andrew Jia-Yi (Penerbit Universiti Kebangsaan Malaysia, 2022)
The COVID-19 pandemic has shown that access to food supply may be a future problem if Malaysia is unable to ensure that food supplies are adequate, of better quality, edible, healthy, nutritious, and at affordable prices. The study examines the level of food security using four dimensions, namely food availability, accessibility, utilisation, and stability. Based on interviews with policymakers and policy document analysis, a framework for food security was created. The results show that if the majority of food products can be produced locally, they may be able to reduce the dependency on imported goods. This increase in availability affects accessibility through lowering prices. The use of biotechnology may further improve food utilisation and stability. These have implications for food production and self-sufficiency levels (SSL). Study shows that achieving high SSL is more about empowering the agriculture sector (to ensure food security) even when food import activities are present. These four dimensions also contribute not only to the food security of the country but also to overall security.